RESPON BEBERAPA VARIETAS TANAMAN JAGUNG (Zea mays L) PADA BERBAGAI SISTEM TANAM - Ahmad Haris Haruna; St. Subaedah; St. Sabahannur (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2018)
This study was conducted with the aim of analyzing the growth and yield of Nasa 29, Bisi 2, and Bima19 URI corn varieties on various planting systems. This research was carried out in the BALITSEREAL Bajeng Experiment Garden, Gowa, South Sulawesi which took place from May to September 2017. The experiments were arranged in the form of Split Plot Design. As the main plot is corn varieties consisting of 3 varieties: NASA 29, Bisi 2, and Bima 19 URI, while the plot is a planting system consisting of two planting systems namely Legowo row planting system and conventional planting system.The results of this study indicate that: Bisi 2 varieties of corn have good growth, which is shown by the highest plant height and has the longest leaves. Nasa 29 varieties produce the longest cob length compared to other varieties. The conventional planting system obtained a larger cob diameter of 46.51 mm compared to the legowo 2:1 cropping system with an average ear diameter of 44.97 mm. The interaction between the Bisi 2 variety and the conventional planting system obtained a cob with the largest cob diameter.